If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + (x + -5) = 2(3 + -1x) Reorder the terms: 4 + (-5 + x) = 2(3 + -1x) Remove parenthesis around (-5 + x) 4 + -5 + x = 2(3 + -1x) Combine like terms: 4 + -5 = -1 -1 + x = 2(3 + -1x) -1 + x = (3 * 2 + -1x * 2) -1 + x = (6 + -2x) Solving -1 + x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -1 + x + 2x = 6 + -2x + 2x Combine like terms: x + 2x = 3x -1 + 3x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 -1 + 3x = 6 + 0 -1 + 3x = 6 Add '1' to each side of the equation. -1 + 1 + 3x = 6 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = 6 + 1 3x = 6 + 1 Combine like terms: 6 + 1 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| 4x^2-28x+c= | | Z+20=6 | | (Xy^2)(x^2+3xy+9)=0 | | 2x^8+6x^8= | | 2(x+6)x^2=90 | | 21x^2y+2xy-8=0 | | 3(x-2)=5(2+3) | | h+h+4=218 | | y=x^5+6x+8 | | 14(y-7)+12y=16-70 | | 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 | | 28u^2-27u-10=0 | | .06(z-300)+.05z=.70z-205 | | 25+30=35+20 | | 0=x^4-4x^3-24x^2+20x+7 | | 5z(x-6y)+7(x-6y)=0 | | 3w-6=20 | | y=abs(4-x) | | -x^2-9x+7=0 | | 3(2x-8)-3=3(X-4)+6 | | x+(x-60)=180 |